Sobre reformas en nuestras Universidades - Giner de los Ríos, Francisco (Historia de las Universidades, 2022)
Written in 1902, on the occasion of the competition "What is the Spanish University today and what should it be in the future", organised by the Universidad de Valencia to celebrate its IV Centenary, this work of Giner's maturity opened the path along which a relevant sector of our historiography on universities has followed.